Lean practices adoption in the Portuguese industry - Diogo Martins; Luis Miguel Ciravegna Martins da Fonseca; Paulo Muniz de Ávila; Jo\~ao Bastos (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: The study purpose was to analyse the excellence and operational efficiency of Portuguese industrial companies through the measurement of lean practices implementation. Additionally, it intended to propose a new model to assess the lean production system. Design/methodology/approach: The research presents an in-depth lean literature review that served as a basis for the creation of a questionnaire. The survey was addressed to Portuguese industrial companies to obtain data about their lean implementation success. Collected data were analysed, resorting descriptive and exploratory statistics. A principal component analysis was applied to reduce the amount of data and define a new model that characterizes the lean practices adoption level. Some Chi-square tests were used to assess the independence of some variables. Findings: The results indicate that a significant percentage of organizations use lean practices within their activity. Concerning the lean implementation maturity, a plus side revealed by the study concerns the adoption of the teamwork, internal information shared principles, increase of process capability to produce conforming products, and reduction in set up times. On the other hand, responsibilities decentralization, more employees acting as team leaders, implementation of employees' suggestions, and interconnection with suppliers, are some of the principles that need to be given greater attention by the Portuguese industrial organizations. The key contribution consists of a new model for lean determinants based on three dimensions: work method, productive process elements, and work efficiency. Originality/value: The present research provides a new Lean determinants model that allows understanding the importance of the operational efficiency provided by a mature lean production system, being the key to the competitiveness in the global business market.
Keywords: 650; lean management; lean tools; lean adoption; Portuguese industry; value